Advances in chromatography. Volume 56 - Grinberg, Nelu, 1950-; Carr, Peter W. (Boca Raton : CRC Press, 2019)
For more than five decades, scientists and researchers have relied on the Advances in Chromatography series for the most up-todate information on a wide range of developments in chromatographic methods and applications. The clear presentation of topics and vivid illustrations for which this series has become known makes the material accessible and engaging to analytical, biochemical, organic, polymer, and pharmaceutical chemists at all levels of technical skill. Key Features: Includes a chapter dedicated to Izaak Maurits Kolthoff, offering a unique look at his non-professional life as well as his impact and legacy in Analytical Chemistry. Discusses recent advances in two-dimensional liquid chromatography for the characterization of monoclonal antibodies and other therapeutic proteins. Reviews solvation processes, methodologies of their measurement, and parameters influenced solvation Explores recent advances in TLC analysis of natural colorings, determination of synthetic dyes, and determination of EU-permitted natural colors, in foods. Offers comprehensive and critical insights on the key aspects of CE-MS analysis of intact proteins
OCLC-licensed vendor bibliographic record.
Keywords: Chromatographic analysis; MEDICAL / Pharmacy; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Analytic